A pilot trial of deferiprone for neurodegeneration with brain iron accumulation - Abbruzzese, G.; Cossu, G.; Balocco, M.; Marchese, R.; Murgia, D.; Melis, M.; Galanello, R.; Barella, S.; Matta, G.; Ruffinengo, U.; Bonuccelli, U.; Forni, G. L. (Haematologica (Roma), 2011)
Deferiprone was shown to reverse iron deposition in Friedreich's ataxia. This multi-center, unblinded, single-arm pilot study evaluated safety and efficacy of deferiprone for reducing cerebral iron accumulation in neurodegeneration with brain iron accumulation. Four patients with genetically-confirmed pantothenate kinase-associated neurodegeneration, and 2 with parkinsonism and focal dystonia, but inconclusive genetic tests, received 15 mg/kg deferiprone bid. Magnetic resonance imaging and neurological examinations were conducted at baseline, six and 12 months. Chelation treatment caused no apparent hematologic or neurological side effects. Magnetic resonance imaging revealed decreased iron accumulation in the globus pallidus of 2 patients (one with pantothenate kinase-associated neurodegeneration). Clinical rating scales and blinded video rating evaluations documented mild-to-moderate motor improvement in 3 patients (2 with pantothenate kinase-associated neurodegeneration). These results underline the safety and tolerability of deferiprone, and suggest that chelating treatment might be effective in improving neurological manifestations associated with iron accumulation. (Clinicaltrials.gov Identifier: NTC00907283).